Pengimplementasian Pembentukan Portfolio Saham Menggunakan Metode Single Index - Yohanes Miracle Chrislie; Andreas Handojo; Lily Puspa Dewi (Jurnal Infra, 2017)
Portfolio using single index models already common made by the players and also the financial consultant. Portfolio of stocks in order to determine what combination of stocks that can be purchased with the expected result is maximum profit with very little risk.But not all the players especially the new players will not understand about the portfolio. Based on these problems, then made a web-based application that can calculate the desired stock portfolio in order to understand whether the stock is favorable or not to optimize the speed of data processing and data entry. Also use the display that is easily understood by the user even if the user is included layman in terms of stocks.The end result of making this application is the calculation that can be justified by proving the truth compared to manual calculation.